2011
DOI: 10.3122/jabfm.2011.02.100162
|View full text |Cite
|
Sign up to set email alerts
|

Performance on the American Board of Family Medicine (ABFM) Certification Examination: Are Superior Test-Taking Skills Alone Sufficient to Pass?

Abstract: Introduction: Certification examinations used by American specialty boards have been the sine qua non for demonstrating the knowledge sufficient for attainment of board certification in the United States for more than 75 years. Some people contend that the examination is predominantly a test of superior test-taking skills rather than of family medicine decision-making ability. In an effort to explore the validity of this assertion, we administered the American Board of Family Medicine (ABFM) Certification to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…5 The study concluded that, although all the participants seem to have performed better than chance would predict, the results affirm the notion that the ABFM board examination is not predominantly a measure of generic test-taking ability and clearly requires medical training to pass. As my father is fond of saying, "failing to plan is like planning to fail."…”
Section: Performance On the American Board Of Family Medicine Certifisupporting
confidence: 68%
See 1 more Smart Citation
“…5 The study concluded that, although all the participants seem to have performed better than chance would predict, the results affirm the notion that the ABFM board examination is not predominantly a measure of generic test-taking ability and clearly requires medical training to pass. As my father is fond of saying, "failing to plan is like planning to fail."…”
Section: Performance On the American Board Of Family Medicine Certifisupporting
confidence: 68%
“…O'Neill et al 5 evaluated whether it was test-taking skills or physician ability that determined a passing score on the ABFM board certification examination. The study was designed using 4 nonphysicians who are considered experts in the field of certification and licensure testing.…”
Section: Performance On the American Board Of Family Medicine Certifimentioning
confidence: 99%
“…31 Simply possessing excellent test-taking skills is insufficient to pass a medical specialty board examination; medical knowledge is essential. 32 Some EM residency graduates delay taking the qualifying examination because they pursue fellowship training (ranging in length from 1 to 3 years). Our study was not designed to identify the experience of these individuals.…”
Section: Discussionmentioning
confidence: 99%
“…2 Through item analysis, a recent study confirmed that the ABFM CE test questions were well written, provided minimal cueing, and required specific medical knowledge as opposed to a generalized test-taking ability to answer questions correctly. 3 To improve performance on the examination, applicants are encouraged to increase their fund of medical knowledge and decision-making ability in clinical scenarios. 4 The Accreditation Council for Graduate Medical Education (ACGME) sets standards for program performance on the ABFM CE.…”
mentioning
confidence: 99%